Assessing health-related knowledge, attitudes and behaviours of HIV-positive Africans accessing services in Gugulethu Township, Cape Town - Zinto, Mantombi Doreen (Stellenbosch : Stellenbosch University, 2011)
Assignment (MPhil)--Stellenbosch University, 2005.